The Role of Interventional Radiology in Urologic Tract Trauma - Mani, Naganathan B.S. (Thieme Medical Publishers, 2011)
The kidney is the third most common abdominal organ to be injured in trauma, following the spleen and liver, respectively. Several classification systems convey the severity of injury to kidneys, ureter, bladder, and urethra. The most commonly used classification scheme is the American Association for the Surgery of Trauma (AAST) classification of blunt renal injuries, which grades renal injury according the size of laceration and its proximity to the renal hilum. Ureteral injury is graded according to its extent relative to the circumference of the ureter and the extent of associated devascularization. Bladder injury is graded according to its location relative to the peritoneum. Urethral injury is graded according to the extent of damage to surrounding anatomic structures. Although these classification schema may not be always used in common parlance, they do help delineate most important features of urologic tract injury that impact patient management and interventions.